Structural changes in a home for aged people aiming the prevention of falls among residents - Silvana Sidney Costa Santos; Danielle Adriane Silveira Vidal; Daiane Porto Gautério; Marília Egues da Silva; Rita Arim Rosales; Marlene Teda Pelzer (Rev Rene)
The aim of this study was to propose changes in the physical structure of a home for aged people aiming the prevention of falls among the residents. It is an Action Research held in Rio Grande do Sul, Brazil, from August 2009 to June 2010. Participants were researchers, administrators and other health workers who had graduated from the institution. Data collection was taken by means of seminar/meeting and semi-structured interview. As a result it was found out that there is distance between the care recommended by the Board Resolution No. 283, September 26, 2005 and Resolution — No. 94, December 31, 2007 of the National Agency of Sanitary Surveillance and genuine capacity to care. The identification of emerging demands of the process of working with the elderly enables the adoption of collective action aimed at preventing falls